Crystal‐chemical investigation of the “cubic Al–Si spinel” issued from the thermal transformation of kaolinite and halloysite - Chauffeton, Christelle; Wallez, Gilles (Journal of the American Ceramic Society, 2022)
Since its discovery in 1959 as a transient nanocrystalline product of the thermal transformation of aluminum‐rich clays, the so‐called Al–Si spinel has been the object of numerous studies aimed at determining its composition. In this work, samples obtained from fired kaolinite‐ and halloysite‐containing clays were analyzed using X‐ray diffraction, leading to conclude in a single cubic (space group Fd‐3m) form, with an unvarying size of crystallites of 5 nm and a constant cell volume, typical of a transition alumina form. Trial‐and‐error Rietveld fitting procedure revealed a crystal structure consisting in an oxygen close packing and a disordered cation sublattice that differs from the known forms of spinel alumina. Rietveld quantitative phase analysis based on this model was successfully implemented on a series of fired halloysite clays, giving a first quantitative insight on the transformations in the 980–1260°C range. The resolution of the crystal structure of the “cubic Al–Si spinel” allows the first quantitative Rietveld analysis of the thermal transformation of kaolinite